Catalyst and method for sulfur-tolerant shift catalytic reaction

By supporting molybdenum oxide, cobalt oxide and cobalt-molybdenum-based perovskite composite oxide on the support, the excessive Mo and Co form a strong interaction with the perovskite and the support is solved, and the problem of the reduction in activity of existing catalysts under low H2S conditions is achieved, and high stability and catalytic activity are improved.

CN116457090BActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180073096.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-27
Filing Date
2021-09-15
Publication Date
2025-03-04
Estimated Expiration
2041-09-15

AI Technical Summary

Technical Problem

The existing cobalt-molybdenum-based sulfur-resistant transformation catalysts have reduced catalytic activity under low H2S content raw material gas conditions, making it difficult to maintain high stability and catalytic activity.

Method used

The catalyst supported by the carrier is used to support molybdenum oxide, cobalt oxide and cobalt-molybdenum-based perovskite composite oxide to form a strong interaction with the perovskite body and support through excessive Mo and Co to improve the stability of the sulfide intermediate.

Benefits of technology

The catalytic performance and stability of the catalyst under low sulfur and low water-gas ratio conditions was significantly improved, high catalytic activity and long life were maintained, and specific surface area was increased to enhance the exposure of active sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116457090B_ABST
    Figure CN116457090B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of sulfur-resistant catalysts, and discloses a catalyst and a preparation method thereof, as well as a method for sulfur-resistant shift catalytic reaction. The catalyst contains a carrier and molybdenum oxide, cobalt oxide and cobalt-molybdenum-based perovskite composite oxide loaded on the carrier, wherein the cobalt-molybdenum-based perovskite composite oxide contains molybdenum element, cobalt element, A element and oxygen element; wherein the A element is one or more of rare earth metal elements, alkali metal elements and alkaline earth metal elements. The catalyst of the present invention also has high sulfur-resistant catalytic activity for feed gas with low H2S content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sulfur-resistant catalysts, and in particular to a catalyst and a method for a sulfur-resistant shift catalytic reaction using the catalyst. Background Art

[0002] Sulfur-resistant conversion is an important way to efficiently utilize coal and is also the main way to produce hydrogen at present. Catalysts are the core of the sulfur-resistant conversion process. Compared with other types of catalysts, cobalt-molybdenum-based catalysts have the advantages of sulfur resistance, wide reaction temperature range, low cost, and simple preparation process. They are the most widely used in domestic and foreign devices.

[0003] Cobalt-molybdenum-based sulfur-tolerant shift catalysts need to have high activity and high stability. In the process of sulfur-tolerant shift reaction using cobalt-molybdenum-based sulfur-tolerant shift catalysts, MoS2 is considered to be the main active component in the sulfur-tolerant shift reaction process, but when the H2S content in the feed gas is low, the catalytic activity of the cobalt-molybdenum-based sulfur-tolerant shift catalyst is significantly reduced.

[0004] Perovskite has excellent electrical conductivity, magnetism, thermoelectricity, piezoelectricity and many other properties, and is inexpensive to prepare, thermodynamically and mechanically stable at high temperatures, and is also an excellent conductor of oxygen ions and electrons under high temperature conditions. However, the specific surface area of ​​the currently prepared perovskite-type sulfur-resistant shift catalyst is relatively low, which severely limits the improvement of the catalytic activity of this type of catalyst. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem of low catalytic activity of sulfur-resistant catalytic reactions in the prior art, especially low catalytic activity of sulfur-resistant catalytic reactions for raw gas with low H2S content, and to provide a catalyst and a method for sulfur-resistant conversion catalytic reaction using the catalyst, wherein the catalyst has high catalytic activity and high stability.

[0006] In order to achieve the above-mentioned purpose, the present invention provides a catalyst on the one hand, which contains a carrier and molybdenum oxide, cobalt oxide and cobalt-molybdenum-based perovskite composite oxide loaded on the carrier, wherein the cobalt-molybdenum-based perovskite composite oxide contains molybdenum element, cobalt element, A element and oxygen element; wherein the A element is one or more of rare earth metal elements, alkali metal elements and alkaline earth metal elements.

[0007] Preferably, element A is one or more of La, Ce, Nd, Gd, Na, K, Mg, Ca, and Sr.

[0008] Preferably, the A element includes an A1 element and an A2 element, the A1 element is one or more rare earth metal elements, and the A2 element is one or more alkali metal elements and alkaline earth metal elements; preferably, the A1 element is one or more La, Ce, Nd, and Gd, and the A2 element is one or more Na, K, Mg, Ca, and Sr; preferably, the molar ratio of the A1 element to the A2 element is 1-99:99-1, preferably 1-9:9-1.

[0009] Preferably, the catalyst shows a characteristic peak at 27.9±0.2° in the XRD spectrum, and preferably shows characteristic peaks at 24.9±0.2°, 27.9±0.2° and 36.2±0.2°.

[0010] Preferably, the main reduction peak temperature of the catalyst in the H2-TPR spectrum is above 600°C, preferably between 600°C and 850°C;

[0011] Preferably, in a temperature-programmed sulfidation test of the catalyst, there are two or more adsorption and desorption peaks at a temperature above 200° C., preferably three or more.

[0012] Preferably, in the catalyst, the content of the A element is 0.4 mol or more and less than 1 mol, preferably 0.4-0.9 mol, and more preferably 0.5-0.9 mol, relative to 1 mol of the total content of the molybdenum element and the cobalt element.

[0013] Preferably, in the catalyst, the content of molybdenum element is greater than 0.4 mol and less than 1 mol, preferably greater than 0.4 mol and less than 0.8 mol, more preferably 0.5-0.6 mol, and further preferably 0.55-0.6 mol, relative to 1 mol of the total content of molybdenum element and cobalt element.

[0014] Preferably, the carrier is alumina, silica, titania, zirconia, magnesia, nickel oxide and a carbon-based carrier or a composite carrier formed by two or more of them, more preferably alumina or a composite carrier formed by alumina and one or more selected from silica, titania, zirconia, magnesia, nickel oxide and a carbon-based carrier.

[0015] Preferably, the carrier accounts for 30-90 mass %, preferably 30-80 mass % in the catalyst.

[0016] Preferably, the specific surface area of ​​the catalyst is 40 m 2 ·g -1 Above, preferably 50m 2 ·g -1 More than 60m 2 ·g -1above.

[0017] A second aspect of the present invention provides a method for a sulfur-resistant shift catalytic reaction, the method comprising: contacting CO in a raw gas with water vapor in the presence of the catalyst of the present invention, wherein the raw gas contains H2S, and the content of H2S is above 100 ppm, preferably 100-1500 ppm.

[0018] The inventors of the present invention have found through in-depth research that perovskite-structured catalysts, when having an appropriate composition, can provide better catalytic performance than traditional catalysts, while still having higher catalytic performance and stronger stability under harsh conditions such as low sulfur and low water-gas ratio.

[0019] On this basis, excess Mo and Co form strong interactions with the perovskite body and the carrier, and there is a synergistic effect between the various phases, which can significantly improve the stability of the sulfide intermediates.

[0020] Therefore, the present invention adds excess cobalt and molybdenum during the process of loading cobalt-molybdenum-based perovskite composite oxide on the surface of the carrier, so that a part of the cobalt and molybdenum forms a perovskite composite oxide with element A, a part of the remaining cobalt and molybdenum adheres to the surface of the perovskite composite oxide, and the other part of the cobalt and molybdenum interacts strongly with the carrier, thereby resulting in a strong synergistic effect between the perovskite structure and the carrier, as well as between cobalt and molybdenum, so that after the catalyst is sulfurized, the sulfide exists stably, and during the reaction process, when the H2S content in the reaction gas is low, the catalyst can have a high stability and will not be deactivated.

[0021] According to a preferred embodiment of the present invention, Al2O3 is a traditional high specific surface area carrier with relatively rich organic groups on its surface. When the active components of the catalyst are dispersed on its surface, its surface and the active components have a strong interaction. If a suitable preparation method is adopted to load the cobalt-molybdenum-based perovskite composite oxide on its surface, it can not only give play to the advantages of the perovskite catalyst, but also make full use of the strong interaction between Al2O3 and the active components, significantly enhance the synergistic effect of the carrier and the perovskite composite oxide, and thus significantly enhance the stability of the sulfide of the sulfur-resistant catalyst during the reaction process.

[0022] The catalyst of the present invention has the following advantages:

[0023] (1) The catalyst of the present invention not only has a high specific surface area and high sulfur-resistant catalytic activity as the perovskite catalyst, but also the cobalt and molybdenum in the catalyst can have a strong interaction with the perovskite composite oxide and the carrier, and there is a synergistic effect between the carrier-perovskite structure-cobalt and molybdenum, so that the catalyst can have high stability and catalyst life under harsh working conditions with low sulfur content, while maintaining high catalytic activity. In addition, the catalyst has a high specific surface area, the exposure of active sites is increased, and the catalytic activity is significantly increased.

[0024] (2) The catalyst of the present invention can be used as a solid sulfur-resistant sulfur conversion catalyst and has high stability and catalyst life even under harsh working conditions with low sulfur content.

[0025] (3) The catalyst preparation process of the present invention is relatively simple, low-cost, easy to operate, and suitable for large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is the XRD spectrum of the catalysts prepared in Example 1 of the present invention and Comparative Examples 3-4.

[0027] Figure 2 It is the H2-TPR spectrum of the catalyst prepared in Examples 1-2 of the present invention and Comparative Example 3.

[0028] Figure 3 It is the TPS spectrum of the catalysts prepared in Example 1 of the present invention and Comparative Examples 3-4.

[0029] Figure 4 The XPS spectra of Mo species in the perovskite catalysts in Example 1, Example 13 and Comparative Example 3 of the present invention are shown.

[0030] Figure 5 The Raman spectra of Mo species in the perovskite catalysts in Example 1 of the present invention and Comparative Example 3 are shown. DETAILED DESCRIPTION

[0031] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0032] On the one hand, the present invention provides a catalyst, which contains a carrier and molybdenum oxide, cobalt oxide and cobalt-molybdenum-based perovskite composite oxide loaded on the carrier, wherein the cobalt-molybdenum-based perovskite composite oxide contains molybdenum element, cobalt element, A element and oxygen element; wherein the A element is one or more of rare earth metal elements, alkali metal elements and alkaline earth metal elements.

[0033] In the present invention, the molybdenum oxide may be any molybdenum oxide, preferably an oxide obtained by calcining a molybdenum salt, such as MoO3, MoO2 or MoO, etc.; the cobalt oxide may be any cobalt oxide, preferably an oxide obtained by calcining a cobalt salt, such as Co3O4, CoO, etc. According to a preferred embodiment of the present invention, the molybdenum oxide is MoO3, and the cobalt oxide is Co3O4.

[0034] In the catalyst of the present invention, the A element is used as a structural additive, and the A element component in any existing perovskite composite oxide (expressed by the general formula ABO3, as a cobalt-molybdenum-based perovskite composite oxide, the B element is Co and Mo) can be used, for example, it can be one or more of rare earth metal elements, alkali metal elements and alkaline earth metal elements. As a rare earth metal element, for example, it can be La, Ce, Nd, Gd, etc.; as an alkali metal element, for example, it can be Na, K, etc.; as an alkaline earth metal element, for example, it can be Mg, Ca, Sr, etc. Among them, the A element is preferably a rare earth metal element and / or an alkaline earth metal element, and more preferably La, Ce, Mg, Ca, Sr, etc.

[0035] According to a preferred embodiment of the present invention, the A element includes an A1 element and an A2 element, wherein the A1 element is one or more rare earth metal elements, and the A2 element is one or more alkali metal elements and alkaline earth metal elements, preferably alkaline earth metal elements. For example, the cobalt-molybdenum-based perovskite composite oxide can be represented by the general formula (A1): x (A2) 1-x BO3 indicates that the B element is Co and Mo, wherein x can be greater than 0.1, greater than 0.15, greater than 0.2, greater than 0.25, greater than 0.3, greater than 0.35, greater than 0.4 or greater than 0.45, and x can be less than 0.95, less than 0.9, less than 0.85, less than 0.8, less than 0.75, less than 0.7, less than 0.65, less than 0.6 or less than 0.55.

[0036] Preferably, the A1 element is one or more of La, Ce, Nd, and Gd, and the A2 element is one or more of Na, K, Mg, Ca, and Sr. By combining the A1 element with the A2 element, the catalytic activity and stability of the catalyst can be further improved.

[0037] Preferably, the molar ratio of A1 element to A2 element is 1-99:99-1, preferably 1-9:9-1, and more preferably 1-2:2-1. By containing A1 element and A2 element in the above ratio, the catalyst of the present invention can further improve the catalytic activity stability of the catalyst.

[0038] The cobalt-molybdenum-based perovskite composite oxide is not particularly limited as long as it has a perovskite structure. Preferably, the content of molybdenum is greater than 0.4 mol and less than 1 mol, more preferably greater than 0.4 mol and less than 0.8 mol, further preferably 0.5-0.6 mol, and further preferably 0.55-0.6 mol, relative to the total content of molybdenum and cobalt 1 mol. z Co 1-z O3 represents, wherein z is greater than 0.4 and less than 1, preferably greater than 0.4 and less than 0.8, more preferably 0.5-0.6, and further preferably 0.55-0.6. From the perspective of further improving the catalytic activity and stability of the catalyst, preferably, in the catalyst, the molar ratio of the molybdenum element to the cobalt element can be 0.5-0.6:0.4-0.5, preferably 0.52-0.56:0.44-0.48.

[0039] In order to ensure that the catalyst contains appropriate amounts of molybdenum oxide, cobalt oxide and cobalt-molybdenum-based perovskite composite oxide, thereby improving its catalytic activity and stability, preferably, in the catalyst, relative to 1 mol of the total content of molybdenum element and cobalt element, the content of element A is greater than 0.4 mol and less than 1 mol, preferably 0.4-0.9 mol, and more preferably 0.5-0.9 mol.

[0040] In the present invention, theoretically, molybdenum and cobalt elements form perovskite composite oxides with element A in a total amount of 1:1 (molar ratio), and the remaining molybdenum and cobalt elements exist in the form of their respective oxides or composite oxides of the two. In view of the current detection means and the actual use effect of the present invention, without being limited by theory, the present invention can ensure that the catalyst contains molybdenum oxide (molybdenum oxide), cobalt oxide (cobalt oxide) and perovskite composite oxide as long as the molybdenum and cobalt elements contained in the catalyst are greater than the stoichiometric amount required to form perovskite composite oxide with element A, and the perovskite composite oxide does not need to be formed in a theoretical amount. As for the accurate content of molybdenum oxide, cobalt oxide and perovskite composite oxide, it does not affect the implementation of the present invention and is within the scope of the present invention.

[0041] According to the present invention, the carrier can be alumina, silica, titania, zirconium dioxide, magnesium oxide, nickel oxide and a carbon-based carrier or a composite carrier formed by two or more thereof. Preferably, the carrier is alumina, silica, titania and zirconium dioxide or a composite carrier formed by two or more thereof. From the perspective of the interaction between molybdenum oxide, cobalt oxide and cobalt-molybdenum-based perovskite composite oxide and the carrier, the carrier preferably contains an aluminum oxide carrier, and more preferably the carrier is alumina, silica, titania, zirconium dioxide, magnesium oxide, nickel oxide and a carbon-based carrier or a composite carrier formed by two or more thereof.

[0042] In addition, in the catalyst of the present invention, the presence form of the alumina carrier is not particularly limited, and can be one or more of α-Al2O3, β-Al2O3, γ-Al2O3 or non-crystalline alumina, as long as it can provide the required catalytic activity. From the perspective of increasing the specific surface area of ​​the catalyst and thus improving the catalytic activity, preferably, the alumina carrier includes at least part of γ-Al2O3. The alumina carrier in the catalyst of the present invention can be formed by an in-situ preparation method. In addition, the catalyst of the present invention can also be obtained by loading the alumina carrier.

[0043] In order to further improve the catalytic activity and stability, in the catalyst, the carrier accounts for 30-90% by mass, preferably 30-80% by mass, and more preferably 50-80% by mass.

[0044] According to the present invention, the specific surface area of ​​the catalyst can be 40m 2 ·g -1 Above, preferably 50m 2 ·g -1 Above or 60m 2 ·g -1 More than 70m 2 ·g -1 Above or 80m 2 ·g -1 More than 90m is more preferred 2 ·g -1 Above or 100m 2 ·g -1 Above, for example 40-180m 2 ·g -1 The specific surface area of ​​the catalyst can be increased by containing a carrier, so the catalyst preferably contains a carrier.

[0045] In the present invention, the perovskite composite oxide and molybdenum oxide, cobalt oxide, cobalt-molybdenum-based perovskite composite oxide and carrier contained in the catalyst can be characterized by methods such as X-ray diffraction (XRD). According to a catalyst of a preferred embodiment of the present invention, in the XRD spectrum, the characteristic peak at 25.5±0.2° shows MoO3, the characteristic peak at 36.2±0.2° shows Co3O4, and the characteristic peak at 27.9±0.2° shows cobalt-molybdenum-based perovskite composite oxide. For the carrier, taking the use of an alumina carrier as an example, according to the different forms of the alumina carrier, it can have characteristic peaks at one or more of 24.9±0.2°, 30.6±0.2°, 35.2±0.2°, 43.3±0.2°, 52.5±0.2°, and 57.5±0.2°.

[0046] According to the present invention, the TPR spectrum of the catalyst shows that the main reduction peak temperature of the catalyst is above 600°C, preferably at 600-850°C, and more preferably at 700-800°C. This shows that the reduction temperature of the reducible species inside the catalyst is mostly above 600°C, and it can be seen that the molybdenum oxide and cobalt oxide inside the catalyst have a strong interaction with the carrier and the perovskite composite oxide. In the present invention, the "main reduction peak temperature" refers to the peak temperature corresponding to the reduction peak with the largest peak area in the TPR spectrum of the catalyst.

[0047] According to the present invention, the temperature-programmed sulfurization (TPS) spectrum of the catalyst shows that in the temperature-programmed sulfurization test of the catalyst, there are more than 2 adsorption and desorption peaks above 200°C, preferably more than 3 adsorption and desorption peaks, and more preferably more than 2 adsorption and desorption peaks (for example, 3-5) in the range of 200°C-600°C (preferably 200-500°C). After sulfurization of the catalyst of the present invention, as the temperature increases, the sulfide decomposition temperature inside the catalyst is higher than 200°C, and multiple adsorption and desorption peaks appear between 200°C and 600°C, which indicates that the sulfide active component formed after the catalyst is sulfurized is relatively stable. According to a preferred embodiment of the present invention, in the temperature-programmed sulfurization test of the catalyst, there are adsorption and desorption peaks in the range of 250-270°C, the range of 330-350°C, and the range of 410-430°C, respectively.

[0048] As the preparation method of the catalyst of the present invention, for example, it can include: forming a gel from a precursor solution including a carrier or a carrier precursor, a molybdenum-containing compound, a cobalt-containing compound, a compound containing an A element, and a complexing agent, and then drying and calcining the gel in sequence, wherein the A element is one or more of a rare earth metal element, an alkali metal element, and an alkaline earth metal element. In this preparation method, the carrier or the carrier precursor can be directly used as a carrier or used to form a carrier, and the molybdenum-containing compound, the cobalt-containing compound, and the compound containing the A element are used together to form the active components of molybdenum oxide, cobalt oxide, and cobalt-molybdenum-based perovskite composite oxide loaded on the carrier. Preferably, the preparation of the carrier and the formation of the active material are completed simultaneously by a one-step method (i.e., the carrier is synthesized by an in-situ preparation method), so as to obtain a structure in which molybdenum oxide, cobalt oxide, and cobalt-molybdenum-based perovskite composite oxide are simultaneously loaded on the carrier.

[0049] In the preparation method of the present invention, the molybdenum-containing compound, the cobalt-containing compound and the compound containing the element A are preferably soluble salts of the corresponding elements (such as nitrates, chlorides, sulfates, acetates, etc.). For example, the molybdenum-containing compound can be one or more of ammonium molybdate, molybdenum nitrate and molybdenum acetate; the cobalt-containing compound can be one or more of cobalt nitrate, cobalt chloride, cobalt acetate and cobalt carbonate; the compound containing the element A can be one or more of lanthanum nitrate, cerium nitrate, neodymium nitrate, gadolinium nitrate, sodium nitrate, potassium nitrate, magnesium nitrate, calcium nitrate and strontium nitrate. Taking an alumina carrier as an example, the carrier or carrier precursor can use an alumina carrier, and the specific aluminum-containing compound can be one or more of aluminum isopropoxide, aluminum nitrate, aluminum acetate, pseudo-boehmite and alumina.

[0050] The precursor solution can be prepared by dissolving its constituent compounds in water. For the mixing method of specific compounds, the above compounds can be directly dissolved in water in sequence, or the aqueous solutions of the compounds can be directly used for mixing. As a preferred mixing order, the carrier or carrier precursor, the molybdenum-containing compound, the cobalt-containing compound, the compound containing the element A or their aqueous solutions can be mixed in sequence, wherein the molybdenum-containing compound and the cobalt-containing compound can also be dissolved at the same time to form an aqueous solution containing molybdenum and cobalt before mixing.

[0051] As a specific example of the method for preparing the above-mentioned precursor solution, the following steps may be included:

[0052] (1) Add the carrier or carrier precursor into deionized water and mix well;

[0053] (2) Add aqueous solutions of compounds containing element A to the mixture obtained in step (1) and mix well.

[0054] (3) respectively dropping an aqueous solution containing a molybdenum compound and an aqueous solution containing a cobalt compound into the mixture obtained in step (2), and mixing them evenly to obtain a new liquid mixture.

[0055] According to the present invention, in order to promote the formation of perovskite composite oxide, the precursor solution also contains a complexing agent. As a complexing agent, it can be one or more of citric acid, EDTA, aminoacetic acid, acrylamide, lactic acid, tartaric acid and hydroxybutyric acid. By adding a complexing agent in the precursor solution, the dispersibility of the active ingredient on the carrier surface can be improved. The organic group contained in the complexing agent can be chelated with the metal, and can effectively promote the interaction between the metals during the reaction process, thereby promoting the formation of the perovskite phase and improving the dispersibility of the active component. Preferably, relative to the total amount of metal ions contained in the precursor solution 1mol, the amount of the complexing agent is 1-4mol, preferably 1-3mol, and more preferably 1-2mol. In addition, in the process of preparing the precursor solution, the complexing agent is preferably added sequentially or simultaneously with the carrier or carrier precursor, for example, in the specific example of preparing the precursor solution above, citric acid is added in step (1).

[0056] From the perspective of improving the catalytic activity and stability of the prepared catalyst, preferably, in the precursor solution, relative to the total amount of 1 mol of the molybdenum-containing compound calculated as molybdenum and the cobalt-containing compound calculated as cobalt, the amount of the molybdenum-containing compound calculated as molybdenum is preferably greater than 0.4 mol and less than 1 mol, more preferably greater than 0.4 mol and less than 0.8 mol, further preferably 0.5-0.6 mol, and further preferably 0.55-0.6 mol. Preferably, the molar ratio of the molybdenum-containing compound calculated as molybdenum to the cobalt-containing compound calculated as cobalt is 0.5-0.6:0.4-0.5, preferably 0.52-0.56:0.44-0.48.

[0057] In order to ensure that the prepared catalyst contains appropriate amounts of molybdenum oxide, cobalt oxide and cobalt-molybdenum-based perovskite composite oxide, preferably, the amount of the compound containing element A calculated as element A is more than 0.4 mol and less than 1 mol, preferably 0.4-0.9 mol, and preferably 0.5-0.9 mol, relative to the total amount of 1 mol of the molybdenum-containing compound calculated as molybdenum and the cobalt-containing compound calculated as cobalt.

[0058] In the present invention, there is no particular limitation on the method for making the precursor solution form a gel, for example, the gel can be obtained by removing at least part of the water in the precursor solution. Specific conditions for forming the gel may include: a temperature of 40-90° C., preferably 60-80° C., more preferably 70-80° C., and a time of 4-24 hours, preferably 5-10 hours, and more preferably 6-8 hours.

[0059] In the present invention, the drying and calcining are not particularly limited, and any equipment and conditions used in catalyst preparation can be used. In order to improve the catalytic activity and stability of the catalyst, the drying conditions may include: a temperature of 60-200°C, preferably 80-150°C, more preferably 80-120°C, and more preferably 80-110°C, and a time of 4-15h, preferably 5-15h, and more preferably 6-12h. The calcining conditions may include: a temperature of 400-1300°C, preferably 500-900°C, more preferably 600-900°C, and a time of 4-48h, preferably 6-12h, and more preferably 8-12h. By drying and calcining under the above conditions, the catalytic activity and stability of the obtained catalyst can be further improved. In addition, from the perspective of increasing the specific surface area of ​​the catalyst and thus improving the catalytic activity and stability, the calcination temperature is preferably 600-700°C.

[0060] The second aspect of the present invention provides a method for sulfur-resistant shift catalytic reaction, which comprises: contacting CO in a raw gas with water vapor in the presence of the catalyst of the present invention; wherein the raw gas contains H2S, and the content of H2S is above 100 ppm, preferably 100-1500 ppm.

[0061] As described above, the catalyst of the present invention is preferably used as a sulfur-resistant shift catalyst. By using the catalyst of the present invention, a good catalytic effect can be achieved when the H2S content of the raw gas is 100 ppm or more (e.g., 100-2000 ppm or 300-2000 ppm). In particular, even if the H2S content in the raw gas is low (e.g., less than 1500 ppm, less than 1000 ppm, less than 800 ppm, less than 600 ppm, or less than 500 ppm), a good CO conversion rate can be obtained.

[0062] The present invention will be described in detail below through examples.

[0063] Example 1

[0064] Take 1.74 mol of aluminum isopropoxide and 2 mol of citric acid and pour them into deionized water, mix them evenly, then take 0.1 mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80°C to evaporate the water for 6 hours, so that it gradually turns into a gel. The obtained gel is dried at 120°C for 12 hours. The dried solid is calcined at 600°C for 8 hours to obtain catalyst C1. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0065] Example 2

[0066] Take 0.64 mol of pseudo-boehmite and 2 mol of citric acid and pour them into deionized water, mix them evenly, then take 0.13 mol of cerium nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.13 mol of ammonium molybdate and 0.13 mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 60°C to evaporate the water for 10 hours, so that it gradually turns into gel. The obtained gel is dried at 120°C for 8 hours. The dried solid is calcined at 800°C for 12 hours to obtain catalyst C2. According to XRF measurement, the final alumina carrier accounts for 40% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 1:1.

[0067] Example 3

[0068] Take 0.48 mol aluminum nitrate and 2 mol citric acid and pour them into deionized water, mix them evenly, then take 0.21 mol magnesium nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.25 mol ammonium molybdate and 0.17 mol cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80°C to evaporate the water for 6 hours, so that it gradually turns into gel. The obtained gel is dried at 120°C for 12 hours. The dried solid is calcined at 600°C for 8 hours to obtain catalyst C3. According to XRF measurement, the final alumina carrier accounts for 30% of the total mass of the catalyst, the molar ratio of Mg element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 0.6:0.4.

[0069] Example 4

[0070] Take 0.91mol aluminum nitrate and 2mol citric acid and pour them into deionized water, mix them evenly, then take 0.11mol calcium nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.12mol ammonium molybdate and 0.1mol cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, heat the precursor solution to 80℃ to evaporate the water for 6h, so that it gradually turns into gel. Dry the obtained gel at 120℃ for 12h. Calcinate the dried solid at 600℃ for 8h to obtain catalyst C4. XRF measured that the final alumina carrier accounted for 60% of the total mass of the catalyst, the molar ratio of Ca element to Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0071] Example 5

[0072] Take 1.54 mol of aluminum isopropoxide and 2 mol of citric acid and pour them into deionized water, mix them evenly, then take 0.1 mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.1 mol of ammonium molybdate and 0.1 mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80°C to evaporate the water for 6 hours, so that it gradually turns into a gel. The obtained gel is dried at 120°C for 12 hours. The dried solid is calcined at 600°C for 8 hours to obtain catalyst C5. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 1:1.

[0073] Example 6

[0074] Take 1.76mol of aluminum isopropoxide and 2mol of citric acid and pour them into deionized water, mix them evenly, then take 0.1mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.12mol of ammonium molybdate and 0.08mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80℃ to evaporate the water for 6h, so that it gradually turns into gel. The obtained gel is dried at 120℃ for 12h. The dried solid is calcined at 600℃ for 8h to obtain catalyst C6. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 0.6:0.4.

[0075] Example 7

[0076] Take 1.81mol of aluminum isopropoxide and 2mol of citric acid and pour them into deionized water, mix them evenly, then take 0.1mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.14mol of ammonium molybdate and 0.06mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80℃ to evaporate the water for 6h, so that it gradually turns into gel. The obtained gel is dried at 120℃ for 12h. The dried solid is calcined at 600℃ for 8h to obtain catalyst C7. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 0.7:0.3.

[0077] Example 8

[0078] Take 1.95mol of aluminum isopropoxide and 2mol of citric acid and pour them into deionized water, mix them evenly, then take 0.13mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.11mol of ammonium molybdate and 0.09mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80℃ to evaporate the water for 6h, so that it gradually turns into gel. The obtained gel is dried at 120℃ for 12h. The dried solid is calcined at 600℃ for 8h to obtain catalyst C8. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:1.5, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0079] Example 9

[0080] Take 1.96mol of aluminum isopropoxide and 2mol of citric acid and pour them into deionized water, mix them evenly, then take 0.15mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.097mol of ammonium molybdate and 0.078mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80℃ to evaporate the water for 6h, so that it gradually turns into gel. The obtained gel is dried at 120℃ for 12h. The dried solid is calcined at 600℃ for 8h to obtain catalyst C9. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:1.2, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0081] Example 10

[0082] Take 1.74 mol of aluminum isopropoxide and 2 mol of citric acid and pour them into deionized water, mix them evenly, then take 0.1 mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80°C to evaporate the water for 6 hours, so that it gradually turns into a gel. The obtained gel is dried at 120°C for 12 hours. The dried solid is calcined at 800°C for 8 hours to obtain catalyst C10. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0083] Embodiment 11

[0084] Take 1.74 mol of aluminum isopropoxide and 2 mol of citric acid and pour them into deionized water, mix them evenly, then take 0.1 mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80°C to evaporate the water for 6 hours, so that it gradually turns into a gel. The obtained gel is dried at 120°C for 12 hours. The dried solid is calcined at 900°C for 8 hours to obtain catalyst C11. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0085] Example 12

[0086] Take 0.87mol α-Al2O3 and 2mol citric acid and pour them into deionized water, mix them evenly to form a suspension, then take 0.1mol lanthanum nitrate aqueous solution and drop it into the above suspension and mix it evenly. Take 0.11mol ammonium molybdate and 0.09mol cobalt nitrate aqueous solutions and drop them into the above suspension respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80℃ to evaporate the water for 6h, so that it gradually turns into a gel. The obtained gel is dried at 120℃ for 12h. The dried solid is calcined at 600℃ for 8h to obtain catalyst C12. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0087] Embodiment 13

[0088] Take 1.48 mol of aluminum isopropoxide and 2 mol of citric acid and pour them into deionized water, mix them evenly, then take 0.05 mol of lanthanum nitrate and 0.05 mol of magnesium nitrate and drop them into the above solution and mix them evenly. Take 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80°C to evaporate the water for 6 hours, so that it gradually turns into a gel. The obtained gel is dried at 120°C for 12 hours. The dried solid is calcined at 600°C for 8 hours to obtain catalyst C13. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of the total of La element and Mg element to the total of Mo element and Co element is 1:2, the molar ratio of La element to Mg element is 1:1, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0089] Embodiment 14

[0090] Take 1.52mol of aluminum isopropoxide and 2mol of citric acid and pour them into deionized water, mix them evenly, then take 0.05mol of lanthanum nitrate and 0.05mol of calcium nitrate and drip them into the above solution and mix them evenly. Take 0.11mol of ammonium molybdate and 0.09mol of cobalt nitrate and drip them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80℃ to evaporate water for 6h, so that it gradually turns into gel. The obtained gel is dried at 120℃ for 12h. The dried solid is calcined at 600℃ for 8h to obtain catalyst C14. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of the total of La element and Ca element to the total of Mo element and Co element is 1:2, the molar ratio of La element to Ca element is 1:1, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0091] Embodiment 15

[0092] 1.64 mol of pseudo-boehmite and 2 mol of citric acid were poured into deionized water and mixed evenly. Then, 0.08 mol of lanthanum nitrate and 0.02 mol of calcium nitrate were dripped into the above solution and mixed evenly. 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate were dripped into the above solution respectively and mixed evenly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours, so that it gradually turned into a gel. The obtained gel was dried at 120°C for 12 hours. The dried solid was calcined at 600°C for 8 hours to obtain catalyst C15. XRF measured that the final alumina carrier accounted for 70% of the total mass of the catalyst, the molar ratio of the total of La element and Ca element to the total of Mo element and Co element was 1:2, the molar ratio of La element to Ca element was 4:1, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0093] Example 16

[0094] 0.25 mol of pseudo-boehmite, 0.26 mol of metatitanic acid and 2 mol of citric acid were poured into deionized water and mixed evenly. Then, 0.05 mol of lanthanum nitrate and 0.05 mol of calcium nitrate were dripped into the above solution and mixed evenly. 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate were dripped into the above solution respectively and mixed evenly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours, so that it gradually turned into a gel. The obtained gel was dried at 120°C for 12 hours. The dried solid was calcined at 600°C for 8 hours to obtain catalyst C16. XRF measured that the final alumina carrier accounted for 70% of the total mass of the catalyst, the molar ratio of the total of La element and Ca element to the total of Mo element and Co element was 1:2, the molar ratio of La element to Ca element was 1:1, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0095] Comparative Example 1

[0096] Take 1.48 mol of aluminum isopropoxide and pour it into deionized water, mix it evenly, then take 0.05 mol of lanthanum nitrate and 0.05 mol of magnesium nitrate in water and drop it into the above solution, mix it evenly. Take 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate in water and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80°C to evaporate the water for 6 hours, so that it gradually turns into a gel. The obtained gel is dried at 120°C for 12 hours. The dried solid is calcined at 600°C for 8 hours to obtain the catalyst DC1. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element and Mg element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0097] Comparative Example 2

[0098] Take 1.22mol of aluminum isopropoxide and 2mol of citric acid and pour them into deionized water, mix them evenly, then take 0.1mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.055mol of ammonium molybdate and 0.045mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80℃ to evaporate the water for 6h, so that it gradually turns into gel. The obtained gel is dried at 120℃ for 12h. The dried solid is calcined at 600℃ for 8h to obtain catalyst DC2. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:1, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0099] Comparative Example 3

[0100] 0.21 mol of ammonium molybdate and 0.17 mol of cobalt nitrate were dissolved in deionized water, and then 2 mol of pseudo-boehmite was impregnated with the above aqueous solution for 12 hours, dried at 120°C for 12 hours, and calcined at 600°C for 8 hours to obtain catalyst DC3. XRF measured that the final alumina carrier accounted for 70% of the total mass of the catalyst, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0101] Comparative Example 4

[0102] Take 124.3g α-Al2O3 and 2mol citric acid and pour them into deionized water, mix them evenly to form a suspension, then take 0.2mol lanthanum nitrate aqueous solution and drop it into the above suspension and mix it evenly. Take 0.11mol ammonium molybdate and 0.09mol cobalt nitrate aqueous solutions and drop them into the above suspension respectively, mix them evenly, and obtain a precursor solution. Then, heat the precursor solution to 80℃ to evaporate the water for 6h, so that it gradually turns into gel. Dry the obtained gel at 120℃ for 12h. Calcinate the dried solid at 600℃ for 8h to obtain catalyst DC4. XRF measured that the final alumina carrier accounted for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element was 1:1, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0103] Comparative Example 5

[0104] Pour 2 mol of citric acid into deionized water and mix well. Then, take 0.1 mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix well. Take 0.055 mol of ammonium molybdate and 0.045 mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix well, and obtain a precursor solution. Then, heat the precursor solution to 80°C to evaporate the water for 6 hours, so that it gradually turns into gel. Dry the obtained gel at 120°C for 12 hours. Calcinate the dried solid at 600°C for 8 hours to obtain catalyst DC5. XRF measured that the molar ratio of La element to Mo element and Co element combined was 1:1, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0105] Comparative Example 6

[0106] Pour 2 mol of citric acid into deionized water and mix well. Then, take 0.1 mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix well. Take 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix well, and obtain a precursor solution. Then, heat the precursor solution to 80°C to evaporate the water for 6 hours, so that it gradually turns into gel. Dry the obtained gel at 120°C for 12 hours. Calcinate the dried solid at 600°C for 8 hours to obtain catalyst DC6. XRF measured that the molar ratio of La element to Mo element and Co element combined was 1:2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0107] Comparative Example 7

[0108] Take 1.1 mol of aluminum isopropoxide and 2 mol of citric acid and pour them into deionized water, mix them evenly, then take 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, heat the precursor solution to 80°C to evaporate the water for 6 hours, so that it gradually turns into a gel. The obtained gel is dried at 120°C for 12 hours. The dried solid is calcined at 600°C for 8 hours to obtain the catalyst DC7. XRF measured that the final alumina carrier accounted for 70% of the total mass of the catalyst, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0109] Comparative Example 8

[0110] Take 53.8g α-Al2O3 and 2mol citric acid and pour them into deionized water, mix them evenly, then take 0.11mol ammonium molybdate and 0.09mol cobalt nitrate aqueous solutions and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, heat the precursor solution to 80℃ to evaporate the water for 6h, so that it gradually turns into gel. Dry the obtained gel at 120℃ for 12h. Calcinate the dried solid at 600℃ for 8h to obtain catalyst DC8. XRF measured that the final alumina carrier accounted for 70% of the total mass of the catalyst, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0111] Comparative Example 9

[0112] Take 1.638 mol of aluminum isopropoxide and pour it into deionized water, mix it evenly, then take 0.1 mol of lanthanum nitrate aqueous solution and drop it into the above solution and mix it evenly. Take 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate aqueous solution and drop them into the above solution respectively, mix them evenly, and obtain a precursor solution. Then, the precursor solution is heated to 80°C to evaporate the water for 6 hours, so that it gradually turns into a gel. The obtained gel is dried at 120°C for 12 hours. The dried solid is calcined at 600°C for 8 hours to obtain catalyst DC9. According to XRF measurement, the final alumina carrier accounts for 70% of the total mass of the catalyst, the molar ratio of La element to Mo element and Co element is 1:2, and the molar ratio of Mo element to Co element is 0.55:0.45.

[0113] Test Example 1

[0114] The XRD characterization of the catalysts prepared in Example 1, Comparative Example 4 and Comparative Example 3 was performed using an X'Pert3 Powder X-ray diffractometer, using a Cu Kα target line (incident wavelength ), the scanning range was 0-90°, the scanning speed was 10° / min, and the obtained spectrum was as follows Figure 1 shown.

[0115] Depend on Figure 1 It can be seen that the catalyst C1 obtained by using Example 1 shows characteristic peaks at 24.9°, 25.5°, 27.9°, 30.6°, 35.2°, 36.2°, 43.3°, 52.5°, and 57.5° in the XRD spectrum. The catalyst DC4 obtained by using Comparative Example 4 shows characteristic peaks at 21.6°, 24.9°, 27.9°, 30.6°, 43.3°, and 47.5° in the XRD spectrum. The catalyst DC3 obtained by using Comparative Example 3 has no obvious characteristic peaks in the XRD spectrum. Among the above characteristic peaks, the characteristic peak at 25.5° shows MoO3, the characteristic peak at 36.2° shows Co3O4, the characteristic peak at 27.9° shows cobalt-molybdenum-based perovskite composite oxide, and the characteristic peaks at 21.6°, 24.9°, 30.6°, 35.2°, 43.3°, 47.5°, 52.5° and 57.5° show Al2O3 carrier.

[0116] Similarly, the catalysts prepared in Examples 2-16 and Comparative Examples 2 and 5-9 were characterized by XRD using the above method. From the measurement results, it can be seen that the XRD patterns of the catalysts prepared in Examples 2-16 of the present invention are similar to the XRD patterns of the catalysts in Example 1, both of which show characteristic peaks of Co3O4, MoO3, cobalt-molybdenum-based perovskite composite oxides and alumina carriers. However, the catalysts in Comparative Examples 1, 3 and 7-9 do not have a perovskite structure.

[0117] Test Example 2

[0118] The H2-TPR spectra of the catalysts prepared in Examples 1-2 and Comparative Example 3 were measured using Tianjin Xianquan TP5080 adsorption instrument. The results are as follows: Figure 2 shown.

[0119] Depend on Figure 2 It can be seen that the main reduction peak temperatures of the catalysts of Examples 1-2 are all in the range of 700-750°C, which are much higher than the main reduction peak temperature of the catalyst of Comparative Example 3 (lower than 400°C), which indicates that the interaction between the active components in the catalyst of the present invention and the perovskite body and the alumina carrier is strong.

[0120] Test Example 3

[0121] In view of the sulfurization behavior of the catalyst, a temperature-programmed sulfurization (TPS) was performed using a Tianjin Xianquan TPS-5096 programmed temperature sulfurizer to measure the sulfurization ability of the catalysts of Example 1 and Comparative Examples 3-4. The results are as follows: Figure 3As shown. The specific determination method is as follows: first weigh 0.3g of 20-mesh catalyst particles, load them into the reaction tube with a funnel, heat them to 40°C at a rate of 10°C / min in a N2 atmosphere, keep it for 30 minutes, and cool it to room temperature. Switch the gas to a 2.0 volume % H2S-98 volume % H2 atmosphere, and heat it to 900°C at a heating rate of 10 / min. The tail gas is detected by TCD.

[0122] Depend on Figure 3 It can be seen that the catalyst C1 of Example 1 has adsorption and desorption peaks at about 261° C., about 340° C., about 418° C., about 647° C., and about 672° C. Compared with the catalyst DC3 of Comparative Example 3 and the catalyst DC4 of Comparative Example 4, the catalyst C1 of Example 1 still has obvious H2S adsorption in the high temperature region, while the catalyst of Comparative Example 3 catalyzes the desorption of H2S in the high temperature region, which indicates that the sulfide intermediate of the catalyst C1 of Example 1 is relatively stable.

[0123] Test Example 4

[0124] XPS characterization was performed on the catalysts prepared in Examples 1, 13 and Comparative Example 3. XPS characterization was performed using an AXIS-ULTRAD L-ray photoelectron spectrometer with a monochromatic Al-Kα target source. Before testing, the samples were pressed into thin sheets and heated at 1×10 -8 The vacuum was drawn under the condition of 1.5477 Pa. To deduct the charging effect, the C1s peak (binding energy of 284.6 eV) of contaminated carbon was used as the calibration standard.

[0125] Depend on Figure 4 It can be seen that the binding energy of Mo species in catalysts C1 and C13 containing perovskite structure is significantly higher than that of Mo species loaded in γ-Al2O3 catalyst. After adding alkaline earth metals to the perovskite structure, the binding energy is further enhanced, which shows that the presence of perovskite makes the Mo surface electrons further missing, and the interaction force of the surrounding environment of Mo species on it is further enhanced. This is also consistent with the results of TPR.

[0126] Test Example 5

[0127] The catalysts prepared in Example 1 and Comparative Example 3 were subjected to Raman spectroscopy testing. Raman spectroscopy testing was performed using a HORIBA LabRAM HR Evolution confocal Raman spectrometer, using a 35mV air-cooled He-Ne laser with an excitation wavelength of 532nm. Raman characterization used 0.1g powder sample (less than 100 mesh) and recorded 400-3000cm -1 Spectrum within the range.

[0128] Depend on Figure 5It can be seen that under the condition of equal MoCo content, there is no characteristic stretching peak of Mo=O in the catalyst DC3 of comparative example 3, and only the characteristic stretching peak of Co=O exists, indicating that the dispersion of Mo species inside the catalyst is high, and part of the Co species exists in the form of particles. In the catalyst C1 of Example 1, there is a characteristic peak of Mo=O, indicating that the aggregation degree of Mo species in this catalyst is high, and it is highly dispersed on the surface of γ-Al2O3, which means that Mo species are highly aggregated on the surface of perovskite. At the same time, it can be seen that the content of Co species on the surface of γ-Al2O3 is significantly reduced, which proves that part of the Co species is distributed on the surface of the perovskite phase.

[0129] Test Example 6

[0130] The carbon monoxide concentration and its change in the tail gas of the catalysts prepared in the above embodiments and comparative examples were tested using a pressurized activity evaluation device to simulate industrial conditions, thereby comparing the catalyst's conversion activity and stability and evaluating the comprehensive performance of the catalyst.

[0131] In the pressurized activity evaluation device, the reaction tube is a stainless steel tube of Ø45×5mm, with a thermocouple tube of Ø8×2mm in the center. A certain amount of water is added according to the water-gas ratio = 1.0, and after high-temperature gasification at 200°C, it is sent into the reaction tube together with the raw gas (the raw gas composition in the two tests: CO = 45 volume%, CO2 = 2 volume%, H2S = 0.15 volume% or 0.05 volume%, and the balance is H2) to carry out water-gas shift reaction. The reaction temperature is 260°C. The tail gas after the reaction is analyzed by chromatography, and the measured results are shown in Table 1.

[0132] In addition, the specific surface area of ​​each catalyst was measured by the BET method. The results are shown in Table 1.

[0133] Table 1

[0134]

[0135] It can be seen from Table 1 above that, compared with the comparative example, the catalyst prepared in the embodiment of the present invention has a higher CO conversion rate in the sulfur-tolerant shift reaction, especially when the H2S content in the feed gas is low, it also has a good CO conversion rate, which shows that the catalyst of the present invention has good catalytic activity in the sulfur-tolerant shift reaction. Even when the H2S content in the reaction gas fluctuates, the catalyst of the present invention can maintain a high CO conversion rate and stability.

[0136] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst, characterized in that The catalyst comprises a carrier and molybdenum oxide, cobalt oxide and cobalt-molybdenum-based perovskite composite oxide loaded on the carrier, wherein the cobalt-molybdenum-based perovskite composite oxide comprises molybdenum element, cobalt element, A element and oxygen element; Wherein, element A is one or more of La, Ce, Nd, Gd, Na, K, Mg, Ca, and Sr; The carrier is alumina or a composite carrier formed by alumina and one or more selected from silicon dioxide, titanium dioxide, zirconium dioxide, magnesium oxide, nickel oxide and carbon-based carriers.

2. The catalyst according to claim 1, wherein The A elements include A1 elements and A2 elements; the A1 elements are one or more of La, Ce, Nd, and Gd, and the A2 elements are one or more of Na, K, Mg, Ca, and Sr.

3. The catalyst according to claim 2, wherein The molar ratio of the A1 element to the A2 element is 1-99:99-1.

4. The catalyst according to claim 3, wherein The molar ratio of the A1 element to the A2 element is 1-9:9-1.

5. The catalyst according to claim 1 or 2, wherein The catalyst shows a characteristic peak at 27.9±0.2° in the XRD spectrum.

6. The catalyst according to claim 5, wherein The catalyst shows characteristic peaks at 24.9±0.2°, 27.9±0.2° and 36.2±0.2° in the XRD spectrum.

7. The catalyst according to claim 1 or 2, wherein In the catalyst, the content of the A element is 0.4 mol or more and less than 1 mol relative to 1 mol of the total content of the molybdenum element and the cobalt element.

8. The catalyst according to claim 7, wherein In the catalyst, the content of the A element is 0.4-0.9 mol relative to 1 mol of the total content of the molybdenum element and the cobalt element.

9. The catalyst according to claim 8, wherein In the catalyst, the content of the A element is 0.5-0.9 mol relative to 1 mol of the total content of the molybdenum element and the cobalt element.

10. The catalyst according to claim 1 or 2, wherein In the catalyst, the content of the molybdenum element is greater than 0.4 mol and less than 1 mol relative to 1 mol of the total content of the molybdenum element and the cobalt element.

11. The catalyst according to claim 10, wherein In the catalyst, the content of the molybdenum element is greater than 0.4 mol and less than 0.8 mol relative to 1 mol of the total content of the molybdenum element and the cobalt element.

12. The catalyst according to claim 11, wherein In the catalyst, the content of the molybdenum element is 0.5-0.6 mol relative to 1 mol of the total content of the molybdenum element and the cobalt element.

13. The catalyst according to claim 12, wherein In the catalyst, the content of the molybdenum element is 0.55-0.6 mol relative to 1 mol of the total content of the molybdenum element and the cobalt element.

14. The catalyst according to claim 1 or 2, wherein The carrier accounts for 30-90% by mass in the catalyst.

15. The catalyst according to claim 14, wherein The carrier accounts for 30-80% by mass in the catalyst.

16. The catalyst according to claim 1 or 2, wherein The specific surface area of ​​the catalyst is 40 m 2 ·g -1 above.

17. The catalyst according to claim 16, wherein The specific surface area of ​​the catalyst is 50 m 2 ·g -1 above.

18. The catalyst according to claim 17, wherein The specific surface area of ​​the catalyst is 60 m 2 ·g -1 above.

19. A method for sulfur-tolerant shift catalytic reaction, characterized in that: The method comprises: contacting CO in a raw gas with water vapor in the presence of a catalyst as described in any one of claims 1 to 18; wherein the raw gas contains H2S, and the content of the H2S is greater than 100 ppm.

20. The catalyst according to claim 19, wherein The H2S content is 100-1500ppm.

Citation Information

Patent Citations

  • Perovskite type sulfur-tolerant shift catalyst as well as preparation method and application thereof

    CN114177912A

  • Porous perovskite type sulfur-tolerant shift catalyst as well as preparation method and application thereof

    CN114425395A